Yttrium-90 Radioembolization in Patients with Hepatocellular Carcinoma Who have Previously Received Sorafenib - Rana, Nitesh; Ju, Andrew W.; Bazylewicz, Michael; Kallakury, Bhaskar; He, Aiwu R.; Unger, Keith R.; Lee, Justin S. (Frontiers in Oncology, 2013)
Purpose: Ytrrium-90 radioembolization (RE) is a locoregional therapy option for hepatocellular carcinoma (HCC). Sorafenib is a multikinase inhibitor used in HCC that can potentially affect the efficacy of RE by altering tumor vascularity or suppressing post-irradiation angiogenesis. The safety and efficacy of sorafenib followed by RE has not been previously reported. Materials and Methods: Patients with HCC who received RE after sorafenib were included in this retrospective review. Overall survival, toxicity, and maximal radiographic response and necrosis criteria were examined. Results: Ten patients (15 RE administrations) fit the inclusion criteria. All were Barcelona Clinic Liver Cancer (BCLC) stage C. Median follow- up was 16.5 weeks. Median overall survival and radiographic progression-free survival were 30 weeks and 28 weeks, respectively. Significant differences in overall survival were seen based on Child-Pugh class (p=0.002) and radiographic response (p=0.009). Three patients had partial response, 6 had stable disease, and 1 had progressive disease. Grade 1 or 2 acute fatigue, anorexia, and abdominal pain were common. Three patients had Grade 3 ascites in the setting of disease progression. Two patients had Grade 3 biochemical toxicity. One patient was sufficiently downstaged following RE and sorafenib to receive a partial hepatectomy. Conclusion: Yttrium-90 radioembolization in patients with hepatocellular carcinoma who have received sorafenib demonstrate acceptable toxicity and rates of radiographic response. However, the overall survival is lower than that reported in the literature on RE alone or sorafenib alone. This may be due in part to more patients in this study having advanced disease compared to these other study populations. Larger prospective studies are needed to determine whether the combination of RE and sorafenib is superior to either therapy alone.